Charge Mapping: Sperm–Particle Interactions and Their Prospects for Charge Mapping (Adv. Biosys. 9/2019). Issue 9 (9th September 2019) - Magdanz, Veronika; Gebauer, Johannes; Sharan, Priyanka; Eltoukhy, Samar; Voigt, Dagmar; Simmchen, Juliane
Abstract : In article number1900061, Veronika Magdanz and co‐workers present the attachment of differently charged microparticles to sperm cells based on electrostatic interactions as a novel technique to study surface charges. The binding of positively and negatively charged particles to distinct regions of the sperm is promising for the creation of charge maps, which gives insight into the dynamic surface change of the cell, an important indicator for a sperm's development.